Rapid Generation of Coronaviral Immunity Using Recombinant Peptide Modified Nanodiamonds - Rostyslav Bilyy; Quentin Pagneux; Nathan François; Galyna Bila; Roman Grytsko; Yuri Lebedin; Alexandre Barras; Jean Dubuisson; Sandrine Belouzard; Karin Séron; Rabah Boukherroub; Sabine Szunerits (Pathogens, 2021)
Vaccination remains one of the most effective tools to prevent infectious diseases. To ensure that the best possible antigenic components are chosen to stimulate a cognitive immune response, boosting antigen presentation using adjuvants is common practice. Nanodiamond-based adjuvants are proposed here as a rapid and versatile platform for antigen conjugation, utilizing peptides common to different pathogenic strains and making this strategy a good candidate for a “ready-to-use” vaccine. Initiation of an inflammatory reaction with a resulting immune response is based on the ability of living organisms to entrap nanostructures such as nanodiamonds with neutrophil extracellular traps (NETs) formation. In this work, coronavirus peptide homological for MERS-CoV, fusion inhibitor, was conjugated to nanodiamonds and used to induce neutrophilic-driven self-limiting inflammation. The resulting adjuvant was safe and did not induce any tissue damage at the site of injection. Mice immunization resulted in IgG titers of ¼,000 within 28 days. Immunization of rabbits resulted in the formation of a high level of antibodies persistently present for up to 120 days after the first immunization (animal lifespan ~3 years). The peptide used for immunization proved to be reactive with sera of convalescent COVID patients, demonstrating the possibility of developing pancoronaviral vaccine candidates.